MODERNIZATION OF THE AIRPORT INFRASTRUCTURE OF UKRAINE IN THE PROCESS OF ADAPTATION OF CIVIL AVIATION LEGISLATION TO INTERNATIONAL AND EUROPEAN STANDARDS - Устинова, Ірина; Чулінда, Людмила (SWorldJournal, 2024)
The article analyzes international and European standards of civil aviation and their influence on the modernization of the airport infrastructure of Ukraine, which becomes one of the factors of increasing the country's capacity for economic growth. The